A dynamic theory of taxation : integrating Kalecki into modern public finance - Laramie, Anthony J.; Mair, Douglas (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2000)
This book provides breakthrough in the analysis of taxation, its incidence and effects on the economy. It provides a coherent framework for the analysis of the effects of different forms of taxation on effective demands, employment, distribution of income and investment.
Includes bibliographical references and index.
gau 17/06/14
Loans
Keywords: Kalecki, Michał; Finance, Public; Taxation